A comparison of ketamine + midazolam to propofol for procedural sedation for lumbar puncture in pediatric oncology by nonanesthesiologists—a randomized comparative trial. Issue 8 (4th May 2018) - Chayapathi, Varsha; Kalra, Manas; Bakshi, Anita S.; Mahajan, Amita
Abstract: Background: Both ketamine–midazolam and propofol are frequently used in pediatric oncology units for procedural sedation. However, there are no prospective, randomized comparative trials (RCT) comparing the two groups when the procedure is performed by nonanesthesiologists. Objective: To compare ketamine + midazolam (group A) and propofol (group B) as sedative agents for intrathecal chemotherapy with regard to efficacy, side effects, time to induction, time to recovery, and smoothness of recovery. Methods: A partially‐blinded RCT was conducted between August 2015 and March 2017 after gaining institutional ethics committee approval. Children aged 1–12 years requiring intravenous sedation for intrathecal chemotherapy were included. Patients were allocated to two treatment arms using computer‐generated randomization tables, after obtaining written consent. The initial doses used were: ketamine 2 mg/kg, midazolam 0.2 mg/kg, and propofol 2.5 mg/kg, as per standard recommendations. The patient, parents, and person analyzing the data were blinded. Time to sedation, dose required, depth of sedation, vital parameters, time and smoothness of recovery, and emergence phenomena were documented. Results: We enrolled 152 patients (76 each in group A and B). Nine patients had a failure of sedation (all in group B). Mean time to sedation and recovery was shorter in group B ( P < 0.001). Transient drop in saturation was more frequent in group B, without statistical significance ( P = 0.174). Mean depth of sedation was greater in group A ( P < 0.001). Emergence symptoms were more frequently experienced in group A ( P < 0.001). Conclusions: Ketamine–midazolam combination is safer and more effective. Propofol is faster in onset and recovery, and has smoother emergence with poor efficacy at recommended initial doses.